Research on side-channel attacks and defense methods for IoT devices - HE Lesheng; FENG Yi; YUE Yuankang; YANG Chongyu; HU Chonghui (Tongxin xuebao)
Internet of things (IoT) devices are typically implemented using microcontrollers with limited computational capabilities, which necessitate the use of lightweight symmetric encryption algorithms to ensure data security. Due to their inherent characteristics, these devices can only be deployed in open environments, making them highly vulnerable to side-channel attacks. To address this issue, experiments were conducted on a self-designed side-channel attack validation platform, where a secure key management scheme and an improved S-box design were proposed as countermeasures against side-channel attacks. The validation platform consisted of a two-stage differential amplifier and an anti-interference finite impulse response (FIR) filter, which were capable of capturing subtle power consumption fluctuations. A two-round correlated energy attack targeting lightweight encryption algorithms was also designed. By evaluating the confidence of the correct key correlation coefficient, after 10 000 attacks on 3 000 power consumption traces of the PRESENT algorithm, a success rate of over 96% is achieved, with the mean correlation of the correct key exceeding 0.6. At a 95% confidence level, a narrow confidence interval is obtained. In contrast, when the improved algorithm is used in the same experiment, the attack success rate is only 9.12%.